New Perspectives in Organization Research (Book). - Zeff, Stephen A.; Gregory, Robert H. (The Accounting Review, 1966)
Reviews the book "New Perspectives in Organization Research," by W.W. Cooper, H.J. Levitt and M.W. Shelly.